The Influence of Business Strategy Elements on Supply Chain Management Implementation in Small and Medium-Sized Enterprises - A.M. Awheda , Abdulghadar; S. Ali, Fareg (Aljameai)
Abstract: Growing market pressure and the increasing globalization of the economy represent a major challenge for SMEs when it comes to effectively presenting their products and services to customers in terms of timing, price and location. This challenge highlights the importance of managing cross-border relationships with business partners and not just focusing on product improvement and production. Supply Chain Management (SCM) has now become a crucial part of the overall strategy for many companies, regardless of their size or industry. However, SMEs in emerging and developing countries face obstacles in implementing SCM due to limited resources and insufficient research in this area. Against this background, this paper examines the factors that influence SMEs’ business strategies when adopting SCM. To achieve the objectives of this research, a questionnaire approach was used to identify and confirm the key elements of business strategy. المستخلص: إن تزايد ضغوط السوق وعولمة الاقتصادات يمثل تحديًا كبيرًا للشركات الصغيرة والمتوسطة في تقديم منتجاتها وخدماتها للعملاء في الوقت المناسب وبالسعر المناسب وفي المكان المناسب. تكمن المشكلة في الحاجة إلى التحكم في العلاقات عبر الحدود بين شركاء الأعمال وتجاوز موقف تحسين المنتج والتصنيع. من أجل الحصول على ميزة تنافسية، أصبحت إدارة سلسلة التوريد جزءًا لا يتجزأ من استراتيجية العديد من الشركات، بغض النظر عن حجمها وصناعتها. ومع ذلك، تواجه الشركات الصغيرة والمتوسطة في البلدان الناشئة والنامية صعوبات في تنفيذ إدارة سلسلة التوريد بسبب نقص الموارد والدراسات العملية في هذا القطاع. وفي ضوء هذه الخلفية، تحدد هذه المخطوطة العناصر التي تؤثر على استراتيجية أعمال الشركات الصغيرة والمتوسطة والتي تربطها مع الشركات الصناعية الكبرى لممارسة إدارة سلسلة الامداد. ولتحقيق أهداف هذه الدراسة تم استخدام طريقة الاستبيان لتحديد والتحقق من العوامل المؤثرة في إستراتيجية العمل.